Tripura Draft Annual Plan 1975-76 Vol - I - Planning Commission (Planning Commission, 1975)
With an area of 10,477 Sq. Km. Tripura is burdened with a large population of 16 lakh persons. The State’s high (population, namely 149 per Sq. km. is quite disproportionate to its level of development. Tripura's topography is mainly hilly, so much so that 60% of the State's area consists of hills and mountains where plough cultivation is not possible. This is a hard fact which brings out in bold relief the intensity of the growing pressure of population with all its crippling affection. economic development of the State.
Tripura